Spatial Variability of Anaerobic Processes and Wastewater pH in Force Mains - Rudelle, Elice Alice (Water environment research : a research publication of the Water Environment Federation, 2016)
The present study focuses on anaerobic organic matter transformation processes in force mains for the purpose of improving existing sewer process models. Wastewater samples were obtained at 100 m intervals from a 1 km long pilot scale force main and measured for several wastewater parameters. Transformation rates for selected parameters were calculated and their spatial variability analyzed. In terms of electron transfer, fermentation was the most significant process, resulting in a net volatile fatty acid formation of 0.83 mmol/L. Sulfate reduction resulted in a production of 0.73 mmol/L of inorganic sulfide. Methanogenesis was negligable in all experiments despite an anaerobic residence time of more than 30 hours. As a result of the anaerobic processes, the wastewater pH decreased by approximately one pH unit, resulting in a corresponding increase in the fraction of molecular hydrogen sulfide. A significant spatial variablilty was observed for the average transformation rates of all parameters